2014
DOI: 10.1080/15325024.2013.831262
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional Forgiveness and PTSD Among Iranian Veterans of the 1980–1988 War

Abstract: The relationship between dispositional forgiveness, empathy, and hope, on the one hand, and posttraumatic stress disorder (PTSD), on the other hand, was examined among Iranian veterans of the Iran-Iraq 1980-1988 conflict. Participants were administered the Forgivingness Questionnaire (measuring lasting resentment, sensitivity to the circumstances of the offense, and unconditional forgiveness), the Empathy Quotient Scale (assessing cognitive empathy, social skills, and emotional reactivity), the Hope Scale (ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
(15 reference statements)
2
10
0
Order By: Relevance
“…All measured forgiveness at dispositional level and had similar findings: One study involving Iranian veterans of the Iran-Iraq 1980-1988 conflict found a negative association between unconditional forgiveness and PTSD symptom severity (Nateghian et al, 2015).…”
Section: Trauma In War Veteransmentioning
confidence: 64%
See 3 more Smart Citations
“…All measured forgiveness at dispositional level and had similar findings: One study involving Iranian veterans of the Iran-Iraq 1980-1988 conflict found a negative association between unconditional forgiveness and PTSD symptom severity (Nateghian et al, 2015).…”
Section: Trauma In War Veteransmentioning
confidence: 64%
“…The studies involving war veterans show a clearer association between forgiveness and PTSD but other factors seem to be at play in the relationship -empathy, hope, anger, negative affect and religious coping to name a few (Karaırmak & Güloğlu, 2014;Nateghian et al, 2015;Witvliet et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24e27 Low forgiveness scores are connected with post-traumatic stress disorder and severe symptoms of anxiety and depression. 28 Numerous studies have tested the relationships among empathy, forgiveness, and QOL; however, a mechanism of forgiveness has not been fully explored. The overall hypothesized model developed in this study was based on the forgiveness as a moderator of biopsychosocial responses and adjustment and empirical evidence obtained from the aforementioned studies (Fig.…”
Section: Introductionmentioning
confidence: 99%